Acute Appendicitis: An Extracolonic Manifestation of Clostridium difficile Colitis - Ali Ridha; Shoaib M. Safiullah; Sarah Al-Abayechi; Amin Ur Rehman Nadeem (Case Reports in Medicine)
The current report is the case of a 30-year-old male patient who presented with symptomatology suggestive of appendicitis. However, careful history-taking and laboratory tests led to the diagnosis of Clostridium difficile colitis, resulting in successful nonsurgical management of this patient. Although both appendicitis and C. difficile colitis are common conditions, they are rarely diagnosed concurrently. This is reflected by paucity of literature describing this manifestation. Given this current presentation, the authors contend that the manifestation of extracolonic colitis within the appendix is possibly underdiagnosed or misdiagnosed as an acute appendicitis and thus potentially results in unnecessary surgical intervention. This report reminds physicians to consider the medical approach to managing acute appendicitis given the possibility of underlying C. difficile colitis as the causative factor.